(untitled) (Journal of Hama University, 2024)
Aim: The aim of this study is to compare the impact of CO2 laser and sandblasting with aluminum oxide granules on translucent zirconia in terms of the bonding strength to resin cement. Materials and Methods: In this in-vitro study 20 translucent zirconia disks (10 mm diameter and 2 mm thickness) were assigned to two groups (n = 10). Group 1: 10 discs were surface treated with CO2 laser , Group 2: 10 discs were surface treated with Sandblasting AL2O3 (50 μm). Dentinal disks were cemented on zirconia disk using dual-curing resin cement. Shear bond strength tests were performed at a crosshead speed of 1 mm/min after 24 hr distilled water storage. Data were analyzed by T Student’s test. Results: The means and standard deviations of shear bond strength values in Group 1, and Group 2 were 1.99, 0.65, 1.93 , 0.54 MPa respectively. The data showed no difference between CO2 laser application and sandblasting with aluminum oxide particles on the shear bond strength between the resin cement and the clear zirconia ceramic (P < 0.05). Conclusions: There was no difference between applying CO2 laser treatment and sandblasting with aluminum granules on translucent zirconia in terms of bond strength with the resin cement.